2016
DOI: 10.12659/pjr.897039
|View full text |Cite
|
Sign up to set email alerts
|

CT Angiographic Evaluation of Pattern and Distribution of Stenosis and its Association with Risk Factors Among Indian Ischemic Stroke Patients

Abstract: SummaryBackgroundStroke is the major cause of disability and third major cause of death. Ischemia causes about 80% of stroke cases; stenosis and occlusion are the predominant cause of stroke. Our purpose for this study was to evaluate the pattern and distribution of stenosis and its association with risk factors in Indian ischemic stroke patients and in other countries, for comparison.Material/MethodsWe evaluated 60 patients after ischemic stroke with CT angiography. The degree of stenosis was measured by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Arterial locations of stenosis: MCA was the predominant location of stenosis (61.1%), followed by PCA (14.8%) in our study, which correlates well with previous observations [9,12]. In MCA,…”
Section: Risk Factors For Carotid Stenosissupporting
confidence: 92%
See 3 more Smart Citations
“…Arterial locations of stenosis: MCA was the predominant location of stenosis (61.1%), followed by PCA (14.8%) in our study, which correlates well with previous observations [9,12]. In MCA,…”
Section: Risk Factors For Carotid Stenosissupporting
confidence: 92%
“…Further, we observed that ICS had an earlier onset as it was more common in the < 60 years age group, whereas ECS occurred in the > 60 years group. Two diagnostic studies performed on different subsets of the Indian population also showed higher representation of ICS-MRA anomalies in individuals affected with stroke, which corroborates our findings [8,9]. In addition, we also observed that stenosis predominantly occurred in males than in females.…”
Section: Age and Occurrence Of Stenosissupporting
confidence: 90%
See 2 more Smart Citations
“…1. ) CTA image analysis CTA diagnosis criteria for Internal Carotid Artery (ICA) stenosis: The degree of carotid stenosis was calculated according to the measurement criteria used in the North American Symptomatic Carotid Endarterectomy Trial (NASCET) [19]. Formula: Stenosis rate (%) = (normal ICA diameter in the distal segment -minimum residual diameter in the stenosis segment) / normal ICA diameter in the distal segment × 100%.…”
Section: Ctp Image Post Processingmentioning
confidence: 99%